Consumption of Nondurable Goods and Contractual Commitment of Disposable Income - Cheng, Pao Lun (The Review of Economics and Statistics, 1963)
Tp wo forces, relatively unimportant several decades ago, have influenced the destiny of the consumer dollar in the years following the Second World War. The first of those forces is the growth of installment and mortgage credit relative to disposable income, and the second is the growth of contractual savings relative to the total amount of personal saving. It is argued in this paper that these two forces, even though stabilizing contractual savings and payments, have altered the pattern of nondurable goods consumption in certain undesirable ways. Since the end of World War II, the phenomenal rise in installment and mortgage credit and its possible de-stabilizing effect on the economy has been a subject of much discussion among economists. But in this paper, our attention is mainly directed to the neglected aspect of how durable goods financing has affected, surreptitiously, the consumption expenditures for nondurable goods and services and how the change may adversely affect the stability of the economy. The change is measured in this paper by comparing two periods the most recent decade, that is, the fifties, and the twenties, a decade selected for statistical convenience as well as for cyclical comparability. The relative importance of these two forces in the two periods and appropriate analytical framework are presented in Section I; the results of empirical investigations and tests are summarized in Section II; and policy implications are examined in Section III.